OpenWRT-Based Proxy Network with GSM Signal Integration using Network Development Life Cycle Method - Nugroho, Rizki Slamet; Yuliansyah, Edy; Maulana, Muhammad Rizki (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
One of the most important discoveries in technological development is the internet. However, infrastructure availability and cost remain a barrier for some. For various needs, in certain circumstances, a cheap and fast connection is required. The purpose of this research is to assist PT Wisata Hutan Lestari, located in Cigobang Hamlet, Karang Tengah Village, Sentul, Bogor Regency, in improving the quality of its services by providing internet access using GSM signals and proxies. To obtain relevant data and results for this research, data collection methods such as literature review and interviews were used. Furthermore, during the implementation phase, the Network Development Life Cycle (NDLC) method was chosen to ensure the success of this month-long research. The study concluded that utilizing GSM signals with the implementation of OpenWRT demonstrated a high level of flexibility in network configuration adjustments and can be implemented in areas with minimal broadband internet access. Furthermore, the use of Trojan.go and vmess proxies on the OpenWRT network improved security and privacy when accessing the internet. Meanwhile, this study can provide several recommendations that can be implemented, such as using Mikrotik to manage bandwidth, adding router devices to expand network coverage, adding modems to increase internet speed, changing or adding to the overall network configuration.